1970
DOI: 10.3181/00379727-133-34639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopamine on the Biological Activity and in Vitro Release of ACTH and FSH

Abstract: Considerable evidence is accumulating suggesting that catecholamines play a role in the regulation of anterior pituitary hormone secretion. In addition to the widespread distribution of noradrenergic nerve terminals in the hypothalamus, there is a particularly prominent group of dopaminergic nerve endings in the median eminence ( 1 ) . Stressful stimuli, such as electric shock, hemorrhage, and hypoglycemia which stimulate ACTH secretion, cause a decrease in brain norepinephrine content ( 2), and norepinephrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…At lower concentrations, no altera tion in release was observed, but at the highest concentrations, all 3 sub stances inactivated ACTH (table I). Similar results have been reported in studies of ACTH release from the PD [Van Loon and Kragt, 1970]. It is not possible, in our experimental model, to define more clearly this effect of the 3 catecholamines on the release of ACTH from the PI (inactivation of ACTH or interference in the ACTH bioassay).…”
Section: Discussionsupporting
confidence: 70%
“…At lower concentrations, no altera tion in release was observed, but at the highest concentrations, all 3 sub stances inactivated ACTH (table I). Similar results have been reported in studies of ACTH release from the PD [Van Loon and Kragt, 1970]. It is not possible, in our experimental model, to define more clearly this effect of the 3 catecholamines on the release of ACTH from the PI (inactivation of ACTH or interference in the ACTH bioassay).…”
Section: Discussionsupporting
confidence: 70%
“…Van Loon & Kragt (1970) found that dopamine denatured FSH in an in-vitro system, and Kamberi, Schneider & McCann (1970) recorded a slight decrease in FSH release at the highest dose of nor¬ adrenaline used in specificity studies with rat pituitary tissue in vitro. The dose used was approximately equivalent to half the dose used in the present experiments.…”
Section: Basal Release Of Lh and Fsh In Vitromentioning
confidence: 97%
“…Side-effects of the drugs could have been responsible and the situation may be resolved by counter-acting these by additional pharmacological means or by in vitro studies. It has been reported that dopamine did not alter basal or stimulated release of ACTH from pituitary tissue in vitro (Van Loon & Kragt, 1970), but those experiments were carried out under almost maximal stress load and with large amounts of catecholamines. Further in vitro studies may delineate the effects of dopamine at hypothalamic and pituitary levels.…”
Section: Ukmentioning
confidence: 98%